PENGARUH BERMAIN PLAY DOUGH TERHADAP KREATIVITAS ANAK TK - Herlina Siwi Widiana, Laelun Hartati (Jurnal Psikologi, 2011)
This research aim to know the influence playing play dough to increase creativity among kindergarten students. The subjects were students of TK ABA Purbayan Kotagede. Data collected by Figural Creativity Test. Gain score is analysed with t -test technique. The result was there is significant influence playing play dough to increase creativity among kindergarten students (t=3,211; p=0,003) . The research result shows that playing play dough effective to increase creativity among kindergarten students.